Effectiveness of training and use of Novasil binder in mitigating aflatoxins in cow milk produced in smallholder farms in urban and periurban areas of Kenya - Anyango, G.; Kagera, I.; Mutua, Florence K.; Kahenya, P.; Kyallo, F.; Andang’o, P.; Grace, Delia; Lindahl, Johanna F. (MDPI, 2021)
Aflatoxins, which commonly contaminate animal feeds and human food, present a major public health challenge in sub-Saharan Africa. After ingestion by cows, aflatoxin B1 is metabolized to aflatoxin M1 (AFM1), some of which is excreted in milk. This study involved smallholder dairy farms in urban and periurban areas of Nairobi and Kisumu, Kenya. The objective was to determine the effectiveness of training and providing farmers with aflatoxin binder (NovaSil®) on AFM1 contamination in raw milk. A baseline survey was undertaken and 30 farmers whose milk had AFM1 levels above 20 ppt were randomly selected for inclusion in the study. Of these, 20 farmers were part of the intervention, and were given training on the usage of the NovaSil® binder, while 10 served as a control group. All farmers were visited biweekly for three months for interviews and milk samples were collected to measure the AFM1 levels. The AFM1 levels were quantified by enzyme linked immunosorbent assay. The NovaSil® binder significantly reduced AFM1 concentrations in the raw milk produced by the farmers in the intervention group over the duration of the study (p < 0.01). The control farms were more likely to have milk with AFM1 levels exceeding the regulatory limit of 50 ppt compared to the intervention farms (p < 0.001) (odds ratio = 6.5). The farmers in the intervention group perceived that there was an improvement in milk yield, and in cow health and appetite. These farmers also felt that the milk they sold, as well as the one they used at home, was safer. In conclusion, the use of binders by dairy farmers can be effective in reducing AFM1 in milk. Further research is needed to understand their effectiveness, especially when used in smallholder settings.